EFFICIENCY AND STUDENT ACADEMIC ACHIEVEMENT - Albert A. Abrosimov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Effective learning activity as a kind of labor activity requires maintaining a high level of efficiency. This ability, along with indicators such as thinking, memory, attention largely determines the success of a student's digestion of educational knowledge. The results of the studies of the educational process in terms of efficiency are -analyzed. Researches were carried out on the basis of experimental data obtained by testing. It was found that the correlations between performance on the Landolt scale and academic performance of students are absent. This result does not mean that there is no relationship between performance and the results of one’s actions. It is obvious that such a relationship exists, however, for its detection it is necessary to choose appropriate research methods and find the parameters that characterize the effectiveness of, inter alia, training. Observations of trainees show that individual natural mechanisms of optimization and adaptation remain undeveloped, and the motivation, interest can only temporarily improve the efficiency of learning. Therefore it is justified the introduction of a special discipline aimed at training on maintaining a high level of efficiency as an effective way to improve the efficiency of not only the learning process, but also to work in a broad sense.